An Evaluation Of The Implementation Hospital Management Information System (SIMRS Transmedic) Using Hot-Fit Method At Hospital Royal Prima Medan - Benedictus Juve; Martin Loodwyck Simanjuntak; Ermi Girsang; Sri Wahyuni Nasution (Sean Institute, 2024)
Entering the digital era, technological developments are increasingly rapid in various fields including the health sector. Information systems have a significant role in organizational success. In an effort to improve health services in hospitals, it is necessary to look at the current performance of SIMRS to find out the positive aspects that encourage system use and identify factors that create obstacles. The aim of this research is to evaluate implementation of the use of a hospital management information system (SIMRS) on user satisfaction at RSU Royal Prima Medan using the HOT -Fit method. This type of research is quantitative research with a Cross Sectional approach. Population in this study consisting of active employees from each division who interact with the system with a total of 432 people. The number of samples in this study was taken from several divisions with a total of 168 samples. Data analysis uses univariate, bivariate and multivariate analysis. The research results show partiallyThere is an influence of system quality, information quality, service quality, organizational structure, facility conditions, and leadership support on user satisfaction of the Hospital Management Information System (SIMRS) at RSU Royal Prima Medan with a p -value < 0.05. Simultaneously or together the independent variables in this study have an effect on users of the Hospital Management Information System (SIMRS) at RSU Royal Prima Medan p-value < 0.05. The independent variable that has the most influence on users of the Hospital Management Information System (SIMRS) at RSU Royal Prima Medan is the leadership support variable. Advice for hospitalsHospitals should evaluate SIMRS more frequently so that they can assess and measure the benefits obtained and find problems that are being faced by users and organizations and can be used as a reference to improve and perfect SIMRS so that it becomes even better.